Heart Rate Responses to Synthesized Affective Spoken Words. (14th August 2012) - Ilves, Mirja; Surakka, Veikko
Abstract : The present study investigated the effects of brief synthesized spoken words with emotional content on the ratings of emotions and heart rate responses. Twenty participants' heart rate functioning was measured while they listened to a set of emotionally negative, neutral, and positive words produced by speech synthesizers. At the end of the experiment, ratings of emotional experiences were also collected. The results showed that the ratings of the words were in accordance with their valence. Heart rate deceleration was significantly the strongest and most prolonged to the negative stimuli. The findings are the first suggesting that brief spoken emotionally toned words evoke a similar heart rate response pattern found earlier for more sustained emotional stimuli.